Diagnostic utility of urinary lipoarabinomannan in pulmonary tuberculosis - Sahar M.T Mourad; Nashwa H Abdelwahab; Alaa El Din A Abdulla; Mona K ElDeeb; Maha Ragab AbdelAzim Ali (Egyptian Journal of Chest Disease and Tuberculosis, 2019)
Background Urinary lipoarabinomannan (LAM) detection is a promising approach for the rapid diagnosis of active tuberculosis (TB). Objective to assess the diagnostic accuracy of quantitative urine Lipoarabinomannan (LAM) test in the diagnosis of pulmonary tuberculosis and evaluate its efficacy as a follow up test after 3 months of the first line of antituberculous therapy. Methods This study was carried out on 40 patients (32 male and 8 female) with active tubercular infection LAM level was measured in urine by enzyme-linked immunosorbant assay (ELISA). Results Patients with smear positive specimens had higher urine LAM level: grade 1+ (mean ± SD of 1.47 ± 0.85 ng/ml), grade 2+ (1.63 ± 1.05 ng/ml), grade 3+ (4.32 ± 2.56 ng/ml) than that of smear negative (1.42 ± 0.50 ng/ml) (P < 0.001). Quantitative urine LAM test results positively correlate with the degree of bacillary burden. Lipoarabinomannan level before treatment (2.74 ± 2.25ng/ml) decreased significantly after 3 months of anti tuberculous treatment (1.28 ± 1.65ng/ml) (p<0.001FNx01). Conclusion Our finding showed that the urine LAM test is simple, rapid, and reliable diagnostic modality for active pulmonary tuberculosis. Quantitative LAM detection results increased progressively with bacillary burden. Urine LAM testing may be an accessible method to monitor response to anti-TB therapy among active pulmonary tuberculosis patients.